A new strategy for integrating superior mechanical performance and high volumetric energy density into a Janus graphene film for wearable solid-state supercapacitors. Issue 39 (26th September 2017) - Song, Zhongqian; Fan, Yingying; Sun, Zhonghui; Han, Dongxue; Bao, Yu; Niu, Li
Abstract : A new strategy for integrating superior mechanical performance and high volumetric energy density into Janus graphene films for wearable solid-state supercapacitors. Abstract : Integration of the contradictory attributes of a well-aligned pore structure and excellent electrical/mechanical properties into graphene-based macroscopic materials perfectly for wearable and portable electronics and energy devices is still a big challenge hitherto. In this study, a simple yet highly efficient reduction and evaporation co-induced self-assembly (RES) method was successfully developed to prepare self-crosslinking Janus graphene films with well-aligned pore and dense shell structures, which endowed the material with excellent electrical conductivity and good mechanical property. Electrochemical studies demonstrate that the graphene films with a thickness of 12.4 μm exhibit an extraordinary volumetric capacitance of 127.7 F cm −3 at a current density of 0.5 mA cm −2, which is superior to that reported in most of the previous studies. The flexible all-solid state supercapacitor based on the Janus graphene films exhibits an ultrahigh energy density of 2.78 mW h cm −3 at 40.3 mW cm −3 as well as a remarkable cycling performance (95.5% of initial capacitance is retained after 10 000 cycles at 2 mA cm −2 ). The fatigue tests further confirm the preferable flexibility and bending and folding capability of the proposed supercapacitor; these are crucial factors to be considered for further wearable applications. These tough and durable supercapacitor devices connected in series have been successfully well-designed into wearable energy storage systems to power small gadgets such as electronic watches and light-emitting diodes. In addition, the microgels formed during the film preparation process are helpful as microgel films can be engraved into micro-supercapacitor patterns that can work as an integrated photodetection system. This strategy can be potentially applied for the design and fabrication of new flexible and portable graphene-based wearable electronic devices.